Improving learning outcomes of locomotor activities through games cats using kodular applications - Lulu Nurajizah; Mohmad Taufik; Sintia Farida; Alexander Fernandes; Musa Musa; Arman Maulana (Mamaos: Journal Physical Education, Sport and Art, 2024)
An increase in basic motion occurs in childhood. As we enter adolescence, our ability to use our motor skills as needed allows us to master increasingly complex movements. The development of motor mastery occurs in line with physical growth, in the early days and the formation of basic movement patterns. Kodular application is a visual mobile application development platform that is easy to use for beginners. The Kodular application is an easy-to-use visual mobile application development platform. This application can help integrate play activities and technology to increase locomotor movement activities in grade V students of SDN Ibu Dewi 5. The results of the implementation of activities and the results of reflection carried out during the process took place in cycle I and cycle II in developing gross motor skills through traditional cat games had a good effect on improving ability. This is proven by the results obtained that show an increase during the activity process, initially achieving a completion percentage of 63.33%. to a percentage of completeness of 96.66%